THE SPECIFIC OF THE ETHNOCULTURAL CIVILIZATIONS PHENOMENON IN THE CONTEXT OF MODERN PHILOSOPHIC INVESTIGATIONS - Харченко, С. П. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the philosophic analysis of the specific of ethnocultural civilizations phenomenon in the context of consideration ethnocultural factors as policultural phenomena is carried out.